2015
DOI: 10.1093/eurpub/ckv029
|View full text |Cite
|
Sign up to set email alerts
|

Cross-national time trends in bullying victimization in 33 countries among children aged 11, 13 and 15 from 2002 to 2010

Abstract: Overall, while still common in many countries, bullying victimization is decreasing. The differences between countries highlight the need to further investigate measures undertaken in countries demonstrating a downward trend.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
148
3
18

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(184 citation statements)
references
References 10 publications
(10 reference statements)
15
148
3
18
Order By: Relevance
“…Our results are in line with cross-national comparisons presented for bullying and also for fighting (14,24). In contrast with the study of Chester et al (14), the methodology of our study covers a wider period of the two decades from 1994 to 2014.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results are in line with cross-national comparisons presented for bullying and also for fighting (14,24). In contrast with the study of Chester et al (14), the methodology of our study covers a wider period of the two decades from 1994 to 2014.…”
Section: Discussionsupporting
confidence: 89%
“…The study by Chester et al (14) showed significant decreasing trends in occasional and chronic victimization between 2001/02 and 2009/10 across both genders in a third of the participating countries. On the contrary, Belgium and Finland reported significant increasing trends for both occasional and chronic victimization.…”
Section: Introductionmentioning
confidence: 94%
“…In an international comparison, Sweden has low rates of bullying (Chester et al, 2015;Craig et al, 2009), and the large-scale data made the analyses possible. However, the study also has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Although surveys with students indicate that the occurrence of bullying has decreased over time in several countries (Chester et al, 2015;Molcho et al, 2009), it continues to be a grave problem, typically having severe consequences for the individual. In an international perspective, Sweden has very low rates of bullying among students (Chester et al, 2015;Craig et al, 2009). Even so, bullying is a significant problem in Sweden, just as in other countries.…”
Section: Introductionmentioning
confidence: 99%
“…Between 2002 and 2010, not only alcohol use, but also the use of tobacco and cannabis declined (Hublet et al, 2015;ter Bogt et al, 2014). Furthermore, young people report healthier eating habits (Vereecken et al, 2015), engage more often in physical activity (Kalman et al, 2015), have fewer injuries (Molcho, Walsh, Donnelly, Gaspar de Matos, & Pickett, 2015), are less likely to be bullied (Chester et al, 2015), more often use contraception when sexually active (Ramiro et al, 2015), and rate their health as 'excellent' more often (Cavallo et al, 2015).…”
Section: A General Trend Toward a Healthier Lifestyle?mentioning
confidence: 99%